2023
DOI: 10.5551/jat.63667
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes and Unique Restenosis of Calcified Nodule in Heavily Calcified Coronary Artery

Abstract: Aims: Calcified nodule (CN) has been known as the advanced stage of coronary calcification. However, clinical outcomes following percutaneous coronary intervention (PCI) to CN remain unknown. This study aimed to compare clinical outcomes, including target lesion revascularization (TLR), between calcified coronary lesions with and without CN. Methods: Two hundred forty-nine lesions undergoing intravascular ultrasound-guided PCI with rotational atherectomy (RA) were enrolled and divided into the CN group (n=100)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…10,21 In our study, the MLA site at follow-up corresponded to the CN site at baseline in 84.6% of the CN group, supporting the hypothesis that CN at index PCI was related to in-stent CNs and subsequent TLR. Moreover, TLRs are reported to predominantly occur within 1 year, 6,10 and in-stent CNs are observed within the same timeframe after stenting. 8 Consistently, in this study, TLR incidence in the CN group was predominantly observed within 1 year.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…10,21 In our study, the MLA site at follow-up corresponded to the CN site at baseline in 84.6% of the CN group, supporting the hypothesis that CN at index PCI was related to in-stent CNs and subsequent TLR. Moreover, TLRs are reported to predominantly occur within 1 year, 6,10 and in-stent CNs are observed within the same timeframe after stenting. 8 Consistently, in this study, TLR incidence in the CN group was predominantly observed within 1 year.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies using intravascular ultrasound (IVUS) identified CN prevalence in 40.0–48.5% of calcified lesions requiring RA. 5,10,17 In this study, we observed CNs in 29.6% of the target lesions using OCT. We defined CNs as eruptive CNs, excluding calcified protrusion (defined without eruptive nodules), as distinguishing between these two types of protruding Ca using IVUS can be challenging. Consistent with our results, several OCT studies demonstrated an association between CN occurrence and older age, renal dysfunction, and hemodialysis.…”
Section: Discussionsupporting
confidence: 51%
“…Calcified nodules were found not to be significant by multi-variate analysis in the study conducted by Fujino et al [ 47 ]. However, recent trials demonstrated that the presence of calcified nodules predicted long-term target lesion revascularization (TLR) and late stent underexpansion, especially within the first year, with higher rates of majopr adverse cardiovascular events (MACE) [ 48 , 49 ]. Another study showed that compared to non-eruptive nodules, nodules of eruptive morphology by OCT were associated with worse post-PCI long-term clinical outcomes, despite better acute stent expansion [ 15 ].…”
Section: Assessment Of the Degree Of Calcificationmentioning
confidence: 99%
“…Five articles comparing CNs versus N-CNs were finally included in our metaanalysis. 12,[25][26][27][28] Characteristics of the included studies Characteristics of the included studies are listed in Table 1. All five included papers comparing CNs versus N-CNs were observational in design.…”
Section: Literature Searchmentioning
confidence: 99%